If it's not what You are looking for type in the equation solver your own equation and let us solve it.
2/3(k-3)=2/3(2k+1)
We move all terms to the left:
2/3(k-3)-(2/3(2k+1))=0
Domain of the equation: 3(k-3)!=0
k∈R
Domain of the equation: 3(2k+1))!=0We calculate fractions
k∈R
(6k2/(3(k-3)*3(2k+1)))+(-6kk/(3(k-3)*3(2k+1)))=0
We calculate terms in parentheses: +(6k2/(3(k-3)*3(2k+1))), so:
6k2/(3(k-3)*3(2k+1))
We multiply all the terms by the denominator
6k2
We add all the numbers together, and all the variables
6k^2
Back to the equation:
+(6k^2)
We calculate terms in parentheses: +(-6kk/(3(k-3)*3(2k+1))), so:We get rid of parentheses
-6kk/(3(k-3)*3(2k+1))
We multiply all the terms by the denominator
-6kk
Back to the equation:
+(-6kk)
6k^2-6kk=0
| X^4-122x^2+121=0 | | 3t+1-8=-3 | | 28-(n-2)=5(n+5) | | x-x/3=7/15 | | 6(x-2)=7x+14 | | 10-3(m+6)=8 | | F(-5)=3x^2+2x-2 | | 55=15^x | | 0=20x-44-2x^2 | | 11y+39=72 | | 44=-7x+4x+8 | | 15-3(x+8)-15=-3 | | 2/3q-7=8 | | 20-3(m-2)=8 | | 7h+3=11 | | 11x+-3=30 | | 3(x-4)-2(x-5)=6+2(x+1)+3x | | Y=20x-44-2x^2 | | -12x+6=-10x-4 | | 2(h+6)-10=4 | | 1=w/136+0.3 | | -3x=143+8x | | -10=5x+7x-10 | | 2x+19=110-5x | | 2x/2-x/3=7/15 | | 9.26p=0.104 | | -9x+7/3-5x+9/3=-5x+1 | | 30x+28x-34=31x+31 | | a(2a+1)=0 | | 3(5x+2)=-7x38 | | 5=3d-4 | | 3|5-6x|-11=13 |